Insight into the Fabrication of ZnAl Layered Double Hydroxides Intercalated with Organic Anions and Their Corrosion Protection of Steel Reinforced Concrete. Issue 16 (3rd December 2019) - Cao, Yanhui; Zheng, Dajiang; Luo, Jingsong; Zhang, Fan; Dong, Shigang; Pan, Jinshan; Lin, Changjian
Abstract : This work provides insight into the fabrication of ZnAl layered double hydroxides (LDHs) intercalated with organic phthalates (PTL) and their corrosion protection of steel reinforced concrete. The structure, composition and morphology of the LDH products prepared by various methods were systematically characterized to find out the relationship of preparation-structure-properties. The ZnAl-LDH-PTL prepared by co-precipitation method presented the best performance of corrosion protection due to its good crystallinity. The corrosion protection mechanism of LDH for steel in concrete system was also discussed.